The rise of radical liberal discourse in Turkish foreign policy - (:unkn) unknown (SETA, 2014)
Change is a central concept in Turkish and global politics. It forms the basis of liberal ideology, alongside freedom, democracy, and equality. In this spirit of change, radical liberal thinkers question the state of contemporary international relations with a focus on justice and fairness. Ahmet Davutoğlu appreciates the importance of these liberal considerations, and he claims the global order is in a period of transformation, in which Turkey and the rest of the world will come into new political roles. In order to facilitate the formation of a fair, cooperative world order, Davutoğlu promotes a global consensus based on cosmopolitanism and multilateralism. These ideas for international reform are consistent with radical liberalism. However, he also considers the formation of a new global order according to his conservative and Islamic ideas—a position inconsistent with liberalism. This contradiction demands a better understanding of Davutoğlu’s stance in domestic politics and international relations, and a consideration of implications for Turkey’s global identity. © 2014, Eflow SETA. All rights reserved.